Customer Perception of New Normal Hygiene Standard Implementation in Café - Daniel Cassa Augustinus; Suci Suksian (Conference Series, 2021)
This research was conducted at D’Raja Coffee Multatuli Medan. This study tries to examine and evaluate the influence of hygiene standard implementation on customers’ perception of service during COVID-19. Data was gathered by the observation, interviews, and questionnaires shared with the consumers. The research sample is 83 respondents. Hygiene Standard Implementation Influences Customers’ Perception in Service at D’Raja Coffee Multatuli Medan. The Coefficient of Determination Test results attained the R squared value is 0.174 which shows that 17.4% of the dependent variable Customers’ Perception in Service at D’Raja Coffee Multatuli Medan can be described through Hygiene Standard Implementation during COVID-19 while they remain 63% is described through the other variables that were not implemented in this research. As the research conclusion is Hygiene Standard Implementation Influences Customers’ Perception of Service during COVID-19 at D’Raja Coffee Multatuli Medan.